Present and future challenges for hydraulic reliability and energy efficiency in collective irrigation systems: A participatory modelling approach - Maria do Rosário Cameira; Antónia Ferreira; Luis Boteta; Pedro Santos Fortes; Maria João Calejo (Agricultural Water Management)
The HubIS project, through a participatory approach with stakeholders, identified the need to assess the hydraulic and energy performance of the Lucefecit Collective Irrigation System (LCIS) for co-designed future scenarios. With this aim, a tool was developed integrating on-farm demand driven water transport and distribution with energy use. The tool results from a participatory modelling process based on the SIGOPRAM software parameterized and tested for the LCIS current conditions (2022) using a comprehensive data set. The current scenario, in which only 48 % of the command area is irrigated, is characterized by good hydraulic performance, although pressure surpluses were detected in most outlets. Co-designed scenarios anticipate an increase in the irrigated area and a shift towards more water-intensive crops, which could result in up to a 163 % in the peak demand flow compared to the current situation. Even in the most demanding scenario, only a few irrigation outlets experience pressure deficits, accounting for 10 % of the irrigable area. Collaborative discussions with stakeholders resulted in a trade-off strategy between hydraulic reliability and energy efficiency. The tool provides the water users associations with an important basis for decision-making supported by system performance assessment, to ensure sustainability in water and energy use while taking in account future climate and agricultural changes.